Introduction to adaptive arrays - Monzingo, Robert A., 1938-; Haupt, Randy L.; Miller, Thomas W. (SciTech Pub., 2011)
This second edition is an extensive modernization of the bestselling introduction to the subject of adaptive array sensor systems. With the number of applications of adaptive array sensor systems growing each year, this look at the principles and fundamental techniques that are critical to these systems is more important than ever before. Introduction to Adaptive Arrays, 2nd Edition is organized as a tutorial, taking the reader by the hand and leading them through the maze of jargon that often surrounds this highly technical subject. It is easy to read and easy to follow, as fundamental concepts are introduced with examples before more current developments and techniques are introduced. Problems at the end of each chapter serve both instructors and professional readers by illustrating and extending the material presented in the text. Both students and practicing engineers will easily gain familiarity with the modern contribution that adaptive arrays have to offer practical signal reception systems.
Keywords: Engineering technologists.; Adaptive antennas.; Antenna arrays.; Signal processing.; elektronické knihy; electronic books